2018
DOI: 10.1016/j.omtn.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Removal of HIV DNA by CRISPR from Patient Blood Engrafts in Humanized Mice

Abstract: We used NOD/SCID mice, also known as NRG, to assess the ability of lentivirus-mediated intravenous delivery of CRISPR in editing the HIV-1 genome from the circulating PBMC engrafts, some of which homed within several animal solid tissues. Lentivirus-mediated delivery of a multiplex of guide RNAs accompanied by Cas9 endonuclease led to the excision of the targeted region of the viral genome positioned within the HIV-1 LTR from the in-vitro-infected human peripheral blood mononuclear cells (PBMCs) embedded in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 23 publications
1
77
0
1
Order By: Relevance
“…A sterilizing cure would require that all HIV-infected cells are targeted with the gRNA and Cas9 components, but reducing the viral load below a certain level may suffice (functional cure). Several delivery methods are available, e.g., for transient editing with gRNA-Cas9 ribonucleoprotein particles or virus-like particles [48][49][50], and for durable editing with adeno-associated virus or lentiviral vectors [17,21,51], but these methods may not reach sufficient infected cells in vivo. Novel delivery methods may be needed that specifically target HIV-reservoir cells, possibly facilitated by a specific marker like CD32a [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…A sterilizing cure would require that all HIV-infected cells are targeted with the gRNA and Cas9 components, but reducing the viral load below a certain level may suffice (functional cure). Several delivery methods are available, e.g., for transient editing with gRNA-Cas9 ribonucleoprotein particles or virus-like particles [48][49][50], and for durable editing with adeno-associated virus or lentiviral vectors [17,21,51], but these methods may not reach sufficient infected cells in vivo. Novel delivery methods may be needed that specifically target HIV-reservoir cells, possibly facilitated by a specific marker like CD32a [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CRISPR/Cas9 has now been used to successfully edit HIV-1 in in vitro-infected primary cells and in PBMCs from ART-suppressed individuals [225]. Multiple studies have also shown the successful application of CRISPR-Cas9 in HIV-1 infected humanized mice [226][227][228][229]. These developments culminated in an interesting humanized mouse study showing that the combination CRISPR/Cas9 and a long-acting slow-effective release ART (LASER ART) achieved apparently complete viral clearance in the absence of any detectable Cas9-mediated off-target effects [229].…”
Section: Crisprmentioning
confidence: 99%
“…76 Similar future efforts will likely rely on CRISPR-based editors, and there is an ongoing push to excise the HIV provirus from infected cells using Cas9. 77 Initial applications of ex vivo therapeutics rely on autologous transplantation, but engineered "universal donor" stem or T cells from healthy donors are being developed using genome editing to enable allogeneic transplantation. 78,79 This approach is appealing because it would eliminate the need for the substantial infrastructure associated with autologous transplantation.…”
Section: Ex Vivo Approachesmentioning
confidence: 99%